União estável e seus efeitos patrimoniais - Kataiama, Ana Carolina Emi Matuoka (2010)
This dissertation held at the Pontifical Catholic University of São Paulo - PUC / SP, aims to show the property in the sphere of civil law in Singapore stable relationships between unmarried couples be prevented from marriage and opting for a stable relationship, bringing an analysis on the applicability or otherwise of Laws no. 8971/94 and 9278/96, compared to the duration of the Civil Code regarding inheritance, housing and real food companions. It presents the concept and legal aspects of family, consisting of the institution of marriage, it is a parallel, bringing them according to their similarity in the stable, established as a family entity in the Federal Constitution and is also subject of this analysis as property regime adopted by partners, and also with regard to freedom of fellow over sixty years, from the absence of specific rules in a stable relationship. Also discussed was the question of whether or not the signature of partner, manage the assets and reflection on the right of the company, demonstrating an understanding of the law, as well as foreign laws that govern on the issue